First record of Aulacaspis tubercularis (Hemiptera: Diaspididae) in Costa Rica, a scale insect affecting mango (Mangifera indica) in Alajuela urban environments - Solano-Gutiérrez, Minor (2023)
Introduction. Mango (Mangifera indica L.) is widely cultivated around the world and in Costa Rica nearly 8200 hectares are dedicated to the production of this crop. More than 400 species of phytophagous insects and mites have been reported on mango worldwide. Among them are around 73 species of armored scale insects (Hemiptera: Diaspididae), of which Aulacaspis tubercularis Newstead is one of the most serious pests of mangos in many parts of the world. Objective. In the present work, we report for the first time the occurrence in Costa Rica of the white mango scale, A. tubercularis. Materials and methods. Mango tree samples were collected in San Rafael, a town located in the central canton of Alajuela province in the Greater Metropolitan Area of Costa Rica. Insects found on leaves were examined under a stereomicroscope, counted and classified according to the condition of their wax covers, which provided evidence of activity by natural enemies. Slide mounts of adult females were prepared and examined under a light microscope. Results. The armored scale was identified as A. tubercularis and the frequency of occurrence on the mango trees sampled was 90%, where 12% of adult females showed evidence of predation and 2.5% showed evidence of parasitization. Conclusion. A. tubercularis was recorded for the first time in Costa Rica. Further investigations on the population dynamics and natural enemies are needed to provide useful information in order to implement adequate control strategies.